PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP WANITA USIA SUBUR TENTANG PEMERIKSAAN IVA TEST - Nisah, Chairun; Ratna Dewi, Eliana, (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
IVA Test is a simple method in early detection of cervical cancer early. The target of IVA Test is WUS aged 15-49 years. In Bengkulu Province WUS who perform the examination of cervical cancer detection by IVA test method is still low. The purpose of this study is to determine the effect of health education on knowledge and attitude of WUS on examination of IVA test in the work area of Sukamerindu Puskesmas Bengkulu City 2017